Radon in Commercial Cigarettes and Associated Health Risks: An Evaluation of Lung Cancer Risk and Radiation Dose in the Kurdistan Region of Iraq - Othman, Sardar Q. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
This study evaluates radon concentrations and associated health risks in 40 commercially available cigarette brands from the Kurdistan Region. Two measurement techniques are employed: RAD-7 (active method) and CR-39 (passive method). Using the CR-39 detector, radon concentrations ranged from 101.99 ± 10.1 Bq·m⁻3 in the S6 (Cigaronne) sample to 339.98 ± 18.44 Bq·m⁻3 in the S32 (Gauloises Gold) sample, with an average concentration of 190.84 ± 13.67 Bq·m⁻3. The RAD-7 measurements show values between 96.01 ± 9.8 Bq·m⁻3 and 282.72 ± 16.81 Bq·m⁻3 in the same samples, averaging 180.30 ± 13.00 Bq·m⁻3. A strong correlation (R² = 0.9271) is observed between the two methods, confirming the reliability of the results. The effective radium content in all cigarette samples remains below internationally recommended safety limits, with Gauloises Gold showing the highest levels. Estimated annual effective doses ranged from 2.57 ± 1.61 mSv·y−1 to 8.58 mSv·y−1, remaining within acceptable limits established by the International Commission on Radiological Protection. Lung cancer risk due to radon exposure varies among brands, with an average of 208 ± 14.27 cases per million individuals. A significant correlation is found between ²²²Rn concentration and estimated annual lung cancer incidence. These findings highlight radon exposure from cigarette smoke as a contributing risk factor for lung cancer, underscoring the need for public health awareness regarding the radiological hazards of smoking.